Case report: Adjuvant therapy with toceranib for an incompletely resected renal cell carcinoma with suspected pulmonary metastasis in a dog - Lee, Da-Eun; Nam, Chang-Hoon; Yoon, Hun-Young; Bae, Kieun; Yoon, Kyong-Ah; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2023)
Primary renal neoplasia is rare in humans and dogs, with renal cell carcinoma (RCC) being the most common form of this cancer. As RCC is often diagnosed at an advanced stage, pulmonary metastasis is frequently observed. Tyrosine kinase inhibitors (TKIs) are the standard adjuvant treatments for metastatic RCC in humans. Similarly, in veterinary medicine, recent trials have employed TKIs for early-stage RCC patients who underwent complete surgical resection and showed no distant metastasis. However, the use of TKIs has not yet been reported commonly in cases of advanced RCC with metastasis. This case study presents the first clinical outcomes of TKI therapy in a dog with incompletely resected RCC and metastasis. A 5-year-old spayed female Chihuahua was referred to our hospital with a right renal mass and multiple pulmonary nodules suspected to be metastases. A portion of the renal mass was surgically removed, and histopathological examination revealed RCC with a high mitotic index. Adjuvant chemotherapy was administered, owing to incomplete resection with suspected pulmonary metastasis. An anticancer drug response prediction test was conducted using patient tissues. Since toceranib showed the most favorable responsiveness, it was selected as a therapeutic agent. Toceranib was orally administered at a dosage of 2.27 mg/kg every 48 h. Regular medical records for potential adverse effects were obtained, including systemic blood pressure, complete blood count, serum biochemical examination, and urinalysis. After 2 weeks of toceranib therapy, partial remission of pulmonary nodules continued for 2 months. The patient did not experience any adverse effects of the anticancer drug during the 4-month follow-up period. However, the patient died from an unidentified cause 6 months after the initial detection of the renal mass. This report describes the use of toceranib in dogs with RCC. In the present case, the patient showed an initial response to chemotherapy, and despite the presence of several poor prognostic factors, the dog survived beyond the expected 3-month lifespan to 6 months. Notably, no adverse events were observed during treatment.